KEBIJAKAN PEMERINTAH, MEDIA, DAN FATWA MUI DALAM MENDINAMISASI PERKEMBANGAN BANK SYARIAH DI INDONESIA - Dwi Purwoko (Sekolah Tinggi Ilmu Pemerintahan Abdi Negara, 2023)
The socio-economic phenomenon in the form of the rapid development of Islamic Islamic banking cannot be separated from government policies that provide support for this development. Regulations regarding the development of Islamic banking have provided a kind of legal certainty for the development of banks which is expected by Muslim communities who seek to invest in a bank that is deemed to be blessed by Allah SWT. The mass media is in the form of electronic media and preachers as a form of mass communication as agents in socializing Islamic banks and has also dynamized the development of Islamic banks in the country. Everything is reinforced by the MUI Fatwa which is a kind of mandatory call to invest as much as possible the Muslim community's money into a sharia bank which is considered a bank that upholds the values of justice and is considered in accordance with sharia principles.